2019
DOI: 10.1016/j.ebiom.2019.02.012
|View full text |Cite|
|
Sign up to set email alerts
|

A PLK1 kinase inhibitor enhances the chemosensitivity of cisplatin by inducing pyroptosis in oesophageal squamous cell carcinoma

Abstract: Background Targeting PLK1 has recently been proven as a viable therapeutic strategy against oesophageal squamous cell carcinom (ESCC). Therefore, this study aimed to explore whether the PLK1 inhibitor BI2536 is able to sensitize ESCC cells to cisplatin (DDP) and determine the underlying mechanisms. Methods Viability, clonogenicity, cell cycle distribution and apoptosis were assessed in ESCC cells treated with BI2536 or DDP alone or in combination. Checkpoint activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
173
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(180 citation statements)
references
References 57 publications
7
173
0
Order By: Relevance
“…The application of a caspase-1 inhibitor can interfere with the expression of NLRP3 and block the production of IL-1β and IL-18 and the release of LDH induced by LPS 103 . In addition, the level of GSDME was more highly in esophageal squamous cell carcinoma (ESCC) than in normal adjacent tissues 104 . miR-214 suppresses cell growth and metastasis by modulating caspase-1-mediated cell pyroptosis in glioma cells 105 .…”
Section: Role Of Pyroptosis In Tumorigenesis and Metastasismentioning
confidence: 99%
“…The application of a caspase-1 inhibitor can interfere with the expression of NLRP3 and block the production of IL-1β and IL-18 and the release of LDH induced by LPS 103 . In addition, the level of GSDME was more highly in esophageal squamous cell carcinoma (ESCC) than in normal adjacent tissues 104 . miR-214 suppresses cell growth and metastasis by modulating caspase-1-mediated cell pyroptosis in glioma cells 105 .…”
Section: Role Of Pyroptosis In Tumorigenesis and Metastasismentioning
confidence: 99%
“…Due to progressive dysphagia, esophageal stenosis, and high resistance to radiotherapy and chemotherapy, it often lost good efficacy 54 . Studies have found that the use of BI2536 which is an ATP-binding domain inhibitor of Polo-like kinase-1 (PLK1), in combination with Cisplatin on esophageal cancer cells can enhance the activity of caspase-3, cause pyroptosis, and in parallel to enhance DNA damage 55 . In addition, Tang et al found that Metformin, a drug widely used in type 2 diabetes, could reduce the expression of Pyruvate kinase isozyme type M2 (PKM2) in esophageal cancer cells.…”
Section: Assosiation Between Caspase-3 Dependent Cell Death and Cancementioning
confidence: 99%
“…For example, a polo-like Kinase 1 (PLK1) inhibitor could sensitize esophageal squamous cell carcinoma (ESCC) cells to cisplatin by inhibiting the DNA damage repair pathway and inducing Bax/caspase3/GSDME pathway-mediated pyroptosis. The new information indicates that PLK1 inhibitor may be an attractive candidate for ESCC targeted therapy, especially when combined with cisplatin for treating GSDME-overexpressing tumors [77]. In a recent study, Fan et al developed a strategy to combine decitabine (DAC) with chemotherapy nanomedicines, triggering tumor cell pyrolysis through epigenetics, thereby further enhancing the immunological effects of chemotherapy.…”
Section: Chemotherapy Drugs-induced Pyroptosis Possesses Anticancer Ementioning
confidence: 99%